Repeated high-dose (5 × 108 TCID50) toxicity study of a third generation smallpox vaccine (IMVAMUNE) in New Zealand white rabbits. Issue 7 (2nd July 2016) - Tree, Julia A.; Hall, Graham; Rees, Peter; Vipond, Julia; Funnell, Simon G. P.; Roberts, Allen D.
ABSTRACT: Concern over the release of variola virus as an agent of bioterrorism remains high and a rapid vaccination regimen is desirable for use in the event of a confirmed release of virus. A single, high-dose (5×10 8 TCID50 ) of Bavarian Nordic's IMVAMUNE was tested in a Phase-II clinical trial, in humans, as a substitute for the standard (1×10 8 TCID50 ), using a 2-dose, 28-days apart regimen. Prior to this clinical trial taking place a Good Laboratory Practice, repeated high-dose, toxicology study was performed using IMVAMUNE, in New Zealand white rabbits and the results are reported here. Male and female rabbits were dosed twice, subcutaneously, with 5×10 8 TCID50 of IMVAMUNE (test) or saline (control), 7-days apart. The clinical condition, body-weight, food consumption, haematology, blood chemistry, immunogenicity, organ-weight, and macroscopic and microscopic pathology were investigated. Haematological investigations indicated changes within the white blood cell profile that were attributed to treatment with IMVAMUNE; these comprised slight increases in neutrophil and monocyte numbers, on study days 1-3 and a marginal increase in lymphocyte numbers on day 10. Macroscopic pathology revealed reddening at the sites of administration and thickened skin in IMVAMUNE, treated animals. After the second dose of IMVAMUNE 9/10 rabbits seroconverted, as detected by antibody ELISA on day 10, by day 21, 10/10 rabbits seroconverted. Treatment-related changes were not detected in other parameters. In conclusion, the subcutaneous injection of 2 high-doses of IMVAMUNE, to rabbits, was well tolerated producing only minor changes at the site of administration. Vaccinia-specific antibodies were raised in IMVAMUNE-vaccinated rabbits only.